Damage mechanism of CFRP laminates with different curvatures impacted by ice projectile at high velocity. (January 2021) - Tang, Enling; Yin, Hetong; Gao, Xingyong; Han, Yafei; Chen, Chuang
Abstract: The spherical ice projectile impacting vertically on Carbon Fiber Reinforced Plastic laminates (CFRP laminates) with different curvatures was developed by using the one-stage light gas gun loading system. The numerical simulation results of the vertical impact of the arched CFRP laminates with different curvatures by SHI were compared with the experimental test results, Scanning Electron Microscopy micro failure mode and the image acquisition of the high speed camera by using ABAQUS/Explicit finite element software. The deformation process and failure mode of arched CFRP laminates with different curvatures and simulated hail ice (SHI)were analyzed, and the reliability of the numerical simulation was verified. By establishing a two-hinged simply supported mechanical physical model of arched laminates, the principal stresses of each layer along the direction of 0° and 90° of fibers in arched laminates were obtained. It would provide technical support for the prediction of fiber failure and delamination damage in the process of impacting on laminates at high velocity. Highlights: Arched CFRP laminates with different curvatures impacted by ice projectile are studied for the first time. The deformation process and failure mode of arched CFRP laminates induced by simulated hail ice（SHI）were analyzed. Under the same impact condition, the crack length, width and damage envelope area increase with the increase of curvature radius. A physical model of two hinges is proposed, and the shear stress of each layer is calculated to predict the delamination of arched laminates.